Protective Effect of Creatine Elevation against Ischaemia Reperfusion Injury Is Retained in the Presence of Co-Morbidities and during Cardioplegia. - Hannah J Whittington; Debra J McAndrew; Rebecca L Cross; Stefan Neubauer; Craig A Lygate (PLoS ONE, 2016)
AIMS:Ischaemic heart disease is most prevalent in the ageing population and often exists with other comorbidities; however the majority of laboratory research uses young, healthy animal models. Several recent workshops and focus meetings have highlighted the importance of using clinically relevant models to help aid translation to realistic patient populations. We have previously shown that mice over-expressing the creatine transporter (CrT-OE) have elevated intracellular creatine levels and are protected against ischaemia-reperfusion injury. Here we test whether elevating intracellular creatine levels retains a cardioprotective effect in the presence of common comorbidities and whether it is additive to protection afforded by hypothermic cardioplegia. METHODS AND RESULTS:CrT-OE mice and wild-type controls were subjected to transverse aortic constriction for two weeks to induce compensated left ventricular hypertrophy (LVH). Hearts were retrogradely perfused in Langendorff mode for 15 minutes, followed by 20 minutes ischaemia and 30 minutes reperfusion. CrT-OE hearts exhibited significantly improved functional recovery (Rate pressure product) during reperfusion compared to WT littermates (76% of baseline vs. 59%, respectively, P = 0.02). Aged CrT-OE mouse hearts (78±5 weeks) also had enhanced recovery following 15 minutes ischaemia (104% of baseline vs. 67%, P = 0.0007). The cardioprotective effect of hypothermic high K+ cardioplegic arrest, as used during cardiac surgery and donor heart transplant, was further enhanced in prolonged ischaemia (90 minutes) in CrT-OE Langendorff perfused mouse hearts (76% of baseline vs. 55% of baseline as seen in WT hearts, P = 0.02). CONCLUSIONS:These observations in clinically relevant models further support the development of modulators of intracellular creatine content as a translatable strategy for cardiac protection against ischaemia-reperfusion injury.